Landscape scale heterogeneity in the East Turkana ecosystem during the Okote Member (1.56–1.38 Ma). Issue 112 (November 2017) - Patterson, D.B.; Braun, D.R.; Behrensmeyer, A.K.; Lehmann, S.B.; Merritt, S.R.; Reeves, J.S.; Wood, B.A.; Bobe, R.
Abstract: Placing the biological adaptations of Pleistocene hominins within a well-resolved ecological framework has been a longstanding goal of paleoanthropology. This effort, however, has been challenging due to the discontinuous nature of paleoecological data spanning many important periods in hominin evolution. Sediments from the Upper Burgi (1.98–1.87 Ma), KBS (1.87–1.56 Ma) and Okote (1.56–1.38 Ma) members of the Koobi Fora Formation at East Turkana in northern Kenya document an important time interval in the evolutionary history of the hominin genera Homo and Paranthropus . Although much attention has been paid to Upper Burgi and KBS member deposits, far less is known regarding the East Turkana paleoecosystem during Okote Member times. This study pairs spatially-resolved faunal abundance data with stable isotope geochemistry from mammalian enamel to investigate landscape-scale ecosystem variability during Okote Member times. We find that during this period 1) taxa within the East Turkana large mammal community were distributed heterogeneously across space, 2) the abundance of C3 and C4 vegetation varied between East Turkana subregions, and 3) the Karari subregion, an area with abundant evidence of hominin stone tool manufacture, had significantly more C3 vegetation than regions closer to the central axis of the Turkana Basin (i.e., Ileret and Koobi Fora). These findings indicate that the East Turkana paleoecosystem during the Okote Member was highly variable across space and provided a complex adaptive landscape for Pleistocene hominins.